Clinical and reproductive pathological changes associated with Brucella melitensis and its lipopolysaccharides in female mice via oral inoculation - Abdullah, Faez Firdaus Jesse; Adamu, Lawan; Adnan, Nur Hazirah; Osman, Abdinasir Yusuf; Mansor, Rozaihan; Haron, Abd Wahid; Saad, Mohd Zamri; Omar, Abdul Rahman; Saharee, Abdul Aziz (Science Publications, 2013)
Brucella melitensis (B. melitensis) are Gram-negative, aerobic, facultative intracellular bacteria that cause brucellosis that usually leads to abortion in sheep and goats. Three groups of equal number of 24 healthy female mice were used as animal models. They were orally inoculated with 0.4 mL of phosphate Buffered Saline (PBS-Control group), 0.4 mL of 109 cfu of B. melitensis and 0.4 mL of Lipopolysaccharides (LPS) extracted from 109cfu of B. melitensis (both as treatment groups). Clinical signs exhibited by the mice were observed for 10 days, after which the survived mice were euthanized by cervical dislocation. Following that, post mortem was conducted and histopathological study of the reproductive organs was carried out. B. melitensis group showed mild clinical signs compared to LPS group which showed normal behaviours except for mild ruffled fur, 14 and 34 h post-inoculation, respectively. The control group (PBS) showed normal behaviours. Histopathology results revealed that both B. melitensis and LPS groups showed mild to moderate infiltration of inflammatory cells in the reproductive organs, along with normal to mild findings of necrosis. Mild to moderate haemorrhage were found in the mice of B. melitensis group, while LPS group showed normal to mild haemorrhage and moderate to severe congestion of the ovary. The study proved that mice infected orally with B. melitensis developed mild clinical signs whereas mice orally inoculated by its LPS showed normal behavior except for the mild ruffled fur. Moreover, both groups of mice inoculated with B. melitensis immunogens developed pathological changes in the reproductive organs. The LPS of B. melitensis could be a potential candidate for the development of vaccines.